Structural semantic and stylistic features of military terms in Uzbek and English languages - Rakhimov Mansur Odiljonovich; A. M Kurganov (Genius Journals, 2021)
The military term is defined as "a stable unit of synthetics of an analytical nomination assigned to the relevant concept in the conceptual and functional system of a certain sphere in profession in the meaning regulated by its definition". This article discusses the structural semantic and stylistic features of military terms in Uzbek and English.
Keywords: Military Terms; Discourse; Structural; Term